Evaluation of a pilot interprofessional Arclight™ workshop for healthcare students in Rwanda: promoting collaborative practice in eye health. Issue 4 (4th July 2021) - O'Carroll, Veronica; Sagahutu, Jean Baptiste; Ndayambaje, Denys; Kayiranga, Dieudonné; Fiston Kitema, Gatera; Rujeni, Nadine; Blaikie, Andrew
ABSTRACT: Preventable and treatable visual impairment affects more than 1 billion people worldwide. Rwanda has an estimated visual impairment prevalence of 3.7% amongst the 12 million inhabitants. Around one third of this demand could be addressed through a more integrated and collaborative approach, particularly in primary eye care services. Healthcare students, therefore, need to be prepared for collaborative practice in eye health through interprofessional learning. Interprofessional workshops were piloted with ophthalmic clinical officer, medical clinical officer, nursing and medical students from the University of Rwanda. The aim was to promote collaborative practice by teaching students how to assess and recognize common eye conditions using the Arclight; a low cost, solar powered, portable ophthalmoscope designed for use in low resource settings. Students reported that the workshop content was relevant to all professional groups. They valued the opportunity to learn interprofessionally, share their knowledge and perspectives, and acquire new knowledge and skills together. This pilot helped to identify the most relevant skills and knowledge for future interprofessional eye health training. It enabled the facilitators to reflect on how best to maintain a balance between a quality interprofessional experience and the more specific eye health related learning objectives.